2017
DOI: 10.1002/cm.21378
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐aligned, single‐shot fiber diffraction using a femtosecond X‐ray free‐electron laser

Abstract: A major goal for X‐ray free‐electron laser (XFEL) based science is to elucidate structures of biological molecules without the need for crystals. Filament systems may provide some of the first single macromolecular structures elucidated by XFEL radiation, since they contain one‐dimensional translational symmetry and thereby occupy the diffraction intensity region between the extremes of crystals and single molecules. Here, we demonstrate flow alignment of as few as 100 filaments (Escherichia coli pili, F‐actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 74 publications
1
7
0
Order By: Relevance
“…Biological polymers that possess helical symmetry represent an intermediate step between 3D crystals and single molecules due to their 1D translational symmetry along the helical axis. To this end, it was recently demonstrated that F-actin microfilaments, amyloid fibrils and pili flow align when injected within a microjet across a focused XFEL beam 31 , with the order of 100 polymers per sample being aligned to within 5°. Similar studies examined and sorted X-ray scattering from crystalline amyloid fibrils 32 and reported diffraction imaging of aligned amyloid fibrils held upon a graphene support 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Biological polymers that possess helical symmetry represent an intermediate step between 3D crystals and single molecules due to their 1D translational symmetry along the helical axis. To this end, it was recently demonstrated that F-actin microfilaments, amyloid fibrils and pili flow align when injected within a microjet across a focused XFEL beam 31 , with the order of 100 polymers per sample being aligned to within 5°. Similar studies examined and sorted X-ray scattering from crystalline amyloid fibrils 32 and reported diffraction imaging of aligned amyloid fibrils held upon a graphene support 33 .…”
Section: Introductionmentioning
confidence: 99%
“…In the specific case at hand here, thanks to the photon energy range delivered by the EuPRAXIA@SPARC_LAB FEL, coherent imaging experiments in the water window will allow obtaining structural information on cells, organelles, viruses and protein aggregates [3][4][5]18] by performing measurements at room temperature and with samples staying in their native state. Exploiting the high degree of transverse coherence of the EuPRAXIA@SPARC_LAB FEL beam, which is foreseen to be between 80% and 100%, 2D images of a variety of biological samples, including bacteria (see Figure 3a), viruses (see Figure 3b), cells, cell organelles and protein aggregates and fibrils [19,20], can be obtained. The possibility of obtaining high resolution structures of fibrils in native conditions is particularly relevant to study the dynamics of their formation, which is important for both industrial/pharmaceutical [21,22] and bio-medical [20] applications.…”
Section: Coherent Imaging Of Biological Samplesmentioning
confidence: 99%
“…& Elser, 2009) is potentially feasible, although the advantage of such an approach is not clear in the case of the relatively strong sampled (Bragg) data in patterns from crystalline fibrils, as opposed to the weak patterns characteristic of singleparticle imaging. We note that Popp et al (2017) used EMC for reorientation of some of their patterns from noncrystalline filaments. In the work reported here, we have averaged the full diffraction patterns in three-dimensional reciprocal space and measured the structure amplitudes from the merged data set.…”
Section: Figure 14mentioning
confidence: 99%
“…XFELs offer significant opportunities for revealing the structural details of these important biological assemblies, due to the possibility of recording diffraction from single fibrils. Popp et al (2017) have recently reported the collection of serial X-ray diffraction data from filament systems at the LCLS using a liquid jet. They observed orientation of the filaments in the jet and were able to perform computational alignment to within 5 in some cases.…”
Section: Introductionmentioning
confidence: 99%